2020
DOI: 10.3171/2020.2.peds19486
|View full text |Cite
|
Sign up to set email alerts
|

Obex position is associated with syringomyelia and use of posterior fossa decompression among patients with Chiari I malformation

Abstract: OBJECTIVEChiari I malformation (CM-I) has traditionally been defined by measuring the position of the cerebellar tonsils relative to the foramen magnum. The relationships of tonsillar position to clinical presentation, syringomyelia, scoliosis, and the use of posterior fossa decompression (PFD) surgery have been studied extensively and yielded inconsistent results. Obex position has been proposed as a useful adjunctive descriptor for CM-I and may be associated with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…9,24,[30][31][32] A recent study by Haller et al found that a low obex position was a stronger predictor than tonsillar ectopia for predicting whether the patient underwent surgery. 33 Also, recently Alford et al showed that greater tonsil length was associated with increased risk for surgery. 34 To our knowledge, however, the present study is the first study to demonstrate that tonsil length is an independent predictor of a more invasive surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…9,24,[30][31][32] A recent study by Haller et al found that a low obex position was a stronger predictor than tonsillar ectopia for predicting whether the patient underwent surgery. 33 Also, recently Alford et al showed that greater tonsil length was associated with increased risk for surgery. 34 To our knowledge, however, the present study is the first study to demonstrate that tonsil length is an independent predictor of a more invasive surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the CVJ is a crucial anatomical location for the onset and decompression of CMIs 31,[34][35][36][37] and based on our previous study about ventral compression, 10 we developed a comprehensive index, the CVJCSI, that can fully reflect the CVJ compression of CMIs to guide treatment. To ensure that the CVJCSI would fully reflect the CVJ compression and data from previous studies, the TH, [23][24][25][38][39][40][41] brainstem hernia (obex option), 6,8,[42][43][44] and CVJ ventral compression 10 were considered as CVJCSI factors.…”
Section: Discussionmentioning
confidence: 99%
“…13 There have been numerous case series of pediatric and adult patients describing clinical presentation and prognosis following surgical procedure, with widely varying surgical outcomes. [14][15][16][17][18] Neither the extent of tonsillar herniation nor the size of the posterior cranial fossa would necessarily predict the presence or resolution of syringomyelia and surgical outcome. 17,[19][20][21] Therefore, there may be other factors playing a role in the pathogenesis and prognosis of syringomyelia.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Neither the extent of tonsillar herniation nor the size of the posterior cranial fossa would necessarily predict the presence or resolution of syringomyelia and surgical outcome. 17,[19][20][21] Therefore, there may be other factors playing a role in the pathogenesis and prognosis of syringomyelia. The morphometric characteristics of the syrinx in CM-I patients may contain different parameters, such as the size, length, configuration, and deviation of the syrinx, while the specific association between morphometric characteristics of syrinx with the prognosis seems to have not been elaborated.…”
Section: Introductionmentioning
confidence: 99%